2020
DOI: 10.1002/mds3.10072
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of silicon dioxide and silicon nitride surfaces with aminosilanes for optical biosensing applications

Abstract: The implementation of sensors for the detection of specific biomolecules from a sample that could contain an enormous number of different molecules, as usually are the biological, environmental or food samples, requires the immobilization of an appropriate recognition element on the transducer surface. Depending on the analyte, the recognition element could be an antibody, an antigen,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…30,31 Moreover, it has already been demonstrated that the thermal treatment at the temperature of 120 °C is crucial to promote the covalent binding of APTES molecules to the hydrophilic surface. 32 We found that, among the different samples analyzed, the surfaces obtained by solution phase deposition of APTES, followed by annealing, and dip coating deposition of CMD, or vapor phase deposition of APTES, followed by annealing treatment, and spin or dip coating deposition of CMD yielded to highest luminescence values (Figure 2b), indicating that the highest level of protein immobilization was reached with these fabrication workflows. Although dip coating is the preferential approach for complex patterns, spin coating resulted in faster and more reliable CMD deposition, including thickness control on the deposited films.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…30,31 Moreover, it has already been demonstrated that the thermal treatment at the temperature of 120 °C is crucial to promote the covalent binding of APTES molecules to the hydrophilic surface. 32 We found that, among the different samples analyzed, the surfaces obtained by solution phase deposition of APTES, followed by annealing, and dip coating deposition of CMD, or vapor phase deposition of APTES, followed by annealing treatment, and spin or dip coating deposition of CMD yielded to highest luminescence values (Figure 2b), indicating that the highest level of protein immobilization was reached with these fabrication workflows. Although dip coating is the preferential approach for complex patterns, spin coating resulted in faster and more reliable CMD deposition, including thickness control on the deposited films.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Moreover, we detected a positive effect of the annealing treatment, performed after the APTES deposition, in all the conditions that we tested. The vacuum thermal process, entailed by the annealing treatment, is capable to promote the selective removal of APTES and OTS molecules that are physiosorbed on the surface but not chemically bound, enhancing the subsequent reproducible deposition of the CMD. , Moreover, it has already been demonstrated that the thermal treatment at the temperature of 120 °C is crucial to promote the covalent binding of APTES molecules to the hydrophilic surface . We found that, among the different samples analyzed, the surfaces obtained by solution phase deposition of APTES, followed by annealing, and dip coating deposition of CMD, or vapor phase deposition of APTES, followed by annealing treatment, and spin or dip coating deposition of CMD yielded to highest luminescence values (Figure b), indicating that the highest level of protein immobilization was reached with these fabrication workflows.…”
Section: Resultsmentioning
confidence: 91%
“…In this regard, hydroxyl based surface tethers have been well studied. However, nitrogen rich surfaces may need the creation of an oxidation layer or silanol groups through oxygen plasma treatment or an alternative tether layer such as positive synthetic amino acid chain like Poly-L-Lysin (PLL) with amine or epoxide based functional groups on the 5' end of the aptamer such that it may react with the amino acid [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…Novel silicon nitride-based nano-photonic waveguides find increasingly application in Raman spectroscopy to enhance signal strength [90] and to miniaturize chips for SERS (surface-enhanced Raman spectroscopy) [91]. Chemical activation of silicon nitride surfaces with either aqueous or organic solutions of 3-aminopropyl triethoxysilane (APTES) led to the development of an optical biosensor allowing for immobilization of biomolecules such as proteins by covalent bonding [92]. Protein immobilization was followed by incubation with murine γ-globulin and reaction with fluorescently labelled goat antimouse IgG antibody.…”
Section: Medical Diagnosticsmentioning
confidence: 99%